A quorum-sensing molecule acts as a morphogen controlling gas vesicle organelle biogenesis and adaptive flotation in an enterobacterium - Ramsay, Joshua; Williamson, N.; Spring, D.; Salmond, G. (2011)
Gas vesicles are hollow intracellular proteinaceous organelles produced by aquatic Eubacteria and Archaea, including cyanobacteria and halobacteria. Gas vesicles increase buoyancy and allow taxis toward air-liquid interfaces, enabling subsequent niche colonization. Here we report a unique example of gas vesicle-mediated flotation in an enterobacterium; Serratia sp. strain ATCC39006. This strain is a member of the Enterobacteriaceae previously studied for its production of prodigiosin and carbapenem antibiotics. Genes required for gas vesicle synthesis mapped to a 16.6-kb gene cluster encoding three distinct homologs of the main structural protein, GvpA. Heterologous expression of this locus in Escherichia coli induced copious vesicle production and efficient cell buoyancy. Gas vesicle morphogenesis in Serratia enabled formation of a pellicle-like layer of highly vacuolated cells, which was dependent on oxygen limitation and the expression of ntrB/C and cheY-like regulatory genes within the gas-vesicle gene cluster. Gas vesicle biogenesis was strictly controlled by intercellular chemical signaling, through an N-acyl homoserine lactone, indicating that in this system the quorum-sensing molecule acts as a morphogen initiating organelle development. Flagella-based motility and gas vesicle morphogenesis were also oppositely regulated by the small RNA-binding protein, RsmA, suggesting environmental adaptation through physiological control of the choice between motility and flotation as alternative taxis modes. We propose that gas vesicle biogenesis in this strain represents a distinct mechanism of mobility, regulated by oxygen availability, nutritional status, the RsmA global regulatory system, and the quorum-sensing morphogen.